System of care and support for independent elderly in the łódzkie voivodship - Potoczna, Małgorzata; Mikołajczyk-Lerman, Grażyna (Problemy społeczne: Trwałość i zmienność w dynamicznej rzeczywistości. Księga jubileuszowa z okazji 45-lecia pracy naukowej i dydaktycznej Profesor Jolanty Grotowskiej-Leder, 2022)
Demographic aging processes reinforce the need for caregiving support for seniors. The number of elderly people requiring long-term assistance is increasing as a result of functional limitations aggravated by increasing life expectancy. The text refers to the issue of institutionalization of the support and care system for the elderly dependent people in the Lodz Voivodeship. The system of care provided to the elderly who, due to limited ability to function independently, require support in meeting their daily needs consists of, on the one hand, support activities provided informally by family members, and on the other hand, in a formal, institutionalized way, care activities are provided by entities located in the social assistance and health care system. Due to the tendencies for deinstitutionalization of care processes, the role of assistance provided at the place of residence of an elderly person, in the form of day care and community care, is increasingly emphasized. The first part of the article presents the demographic and social determinants of the structure of care needs of dependent elderly people and the existing resources of institutional and community-based support for the elderly in the phase of dependency. The second part presents the basic difficulties and problems faced by selected institutions supporting the elderly in the course of everyday implementation of care tasks, as part of long-term care and day and community care in the province of Lodz. These include problems associated with the provision of an adequate range of support for the charges, limitations that hinder the process of assessment of dependence, estimation of assistance and care needs, or problems of adaptation of the charges resulting from loneliness, depression, limited or no contact with the family, which hinder the care process. The analyses presented in this part of the article are based on empirical material collected within a research project entitled Dependent People in Lodz Voivodeship carried out on behalf of the Regional Social Integration Observatory in Lodz in selected institutions providing care and health services for adults who require more support due to their age, health condition or disability.